Application of Exogenous dsRNAs-induced RNAi in Agriculture: Challenges and Triumphs - Das, Protiva Rani; Sherif, Sherif M. (Frontiers in Plant Science, 2020)
In recent years, RNA interference (RNAi) machinery has widely been explored by plant biologists for its potential applications in disease management, plant development, and germplasm improvement. RNAi-based technologies have mainly been applied in the form of transgenic plant generation and host-induced-gene-silencing (HIGS). However, the approval of RNAi-based transgenic plants has always been challenging due to the proclaimed concerns surrounding their impacts on human health and the environment. Lately, exogenous applications of double-stranded RNAs (dsRNAs), short interfering RNAs (siRNAs), and hairpin RNAs (hpRNAs) has emerged as another technology that could be regarded as more eco-friendly, sustainable, and publicly acceptable than genetic transformation. Inside the plant cell, dsRNAs can undergo several steps of processing, which not only triggers RNAi machinery but may also involve transitive and systemic silencing, as well as epigenetic modifications. Therefore, along with the considerations of proper exogenous applications of dsRNAs, defining their final destination into plant cells is highly relevant. In this review, we highlighted the significance of several factors that affect dsRNA-induced gene silencing, the fate of exogenous dsRNAs in the plant cell, and the challenges surrounding production technologies, cost-effectiveness, and dsRNAs stability under open-field conditions. This review also provided insights into the potential applications of exogenous dsRNAs in plant protection and crop improvement.